2015
DOI: 10.1063/1.4905377
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation enhanced vibrational sensing in an olfactory molecular switch

Abstract: Motivated by a proposed olfactory mechanism based on a vibrationally-activated molecular switch, we study electron transport within a donor-acceptor pair that is coupled to a vibrational mode and embedded in a surrounding environment. We derive a polaron master equation with which we study the dynamics of both the electronic and vibrational degrees of freedom beyond previously employed semiclassical (MarcusJortner) rate analyses. We show: (i) that in the absence of explicit dissipation of the vibrational mode,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…They found that the rate of odorant-mediated inelastic ET is larger than the rate of elastic one. Following this approach, in a very recent work, Chȩcińska and co-workers examined dynamically dissipative role of environment in vibration-based olfactory recognition and showed that the strong coupling to the environment can enhance the odorant frequency resolution in the ET rates [11].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the rate of odorant-mediated inelastic ET is larger than the rate of elastic one. Following this approach, in a very recent work, Chȩcińska and co-workers examined dynamically dissipative role of environment in vibration-based olfactory recognition and showed that the strong coupling to the environment can enhance the odorant frequency resolution in the ET rates [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Reese et al (81) addressed several of these concerns, showing that the binding effects of the receptor have a nonzero-all but negligible-effect on the ligand, that dynamic fluctuations have a very small effect on the transfer, and that the reorganization energy (λ) for an OR can conform to λ 1 kcal/mol. Concerns of electron density leaking into the environment were previously addressed through coupling a vibrational bath with the electron transfer (80), and such studies have shown that environmentalinduced dissipation could enhance the vibrational signaling (82). Evaluating the reliability of the electron delivery mechanism cannot be addressed until the complete structure of the OR is known and models account for all cofactors including the possible effects of perireceptor molecular species, as there is evidence that NADPH and other oxidative processes are important in GPCR activation (59).…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…Thus, a molecule must both fit into the active site with the correct orientation and have a vibrational mode capable of assisting in an IET process to activate the protein. Working within Turin's hypothesis, several theoretical expansions have been undertaken to account for specific considerations of the system, including charge transfer rates (60,80), receptor effects (80)(81)(82), and chiral effects (83).…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…However, for the reverse process the odourant must provide the energy. Since the odourant will re-equilibrate with the receptor very rapidly after excitation [55], the reverse process is frustrated. Thus we can ignore any coherence between the electron jumping from D to A and the reverse process, and so can describe it in terms of a transition rate.…”
Section: Appendix 1 Derivation Of the Vibrational Rate Equationmentioning
confidence: 99%
“…Of course, at equilibrium the same argument holds for the electrons; however, there are electrochemical processes that operate in living cells that can generate electrons of increased energy. We note that immediately following the transition, the molecule is in a vibrationally excited state, so the reverse process is then rapid; however, this can be suppressed by interactions of the molecule with its environment [55]. (3) Third, D and A and must not be coupled strongly to their environment:…”
Section: Turin Theorymentioning
confidence: 99%